Gender Awareness of Maria Hartiningsih as Kompas Reporter - Rajab Ritonga; Endah Murwani; Syafruddin Ritonga (Ikatan Sarjana Komunikasi Indonesia, 2017)
Structure of the media in Indonesia is still dominated by men who lack of gender sensitivity so that the role of women journalists as agents of change towards gender awareness is important to discuss. This study aims to determine the factors that make up the awareness, values and attitudes of women journalists on gender, and the influence of media and community structure in forming the gender awareness of women journalists. As a case study, a journalist of the largest newspaper in Indonesia, Kompas, namely Maria Hartiningsih is chosen. The study is based on the concept of gendered-perspective journalism as a practice of journalistic that informs and questions inequality of the relationship between men and women. The study uses a qualitative approach with the method of Critical Discourse Analysis model of Norman Fairclough. Text analysis is conducted to examine the writings of Maria Hartiningsih in Kompas related to gender issues. The results show that at the textual level—since she started joining Kompas—Maria Hartiningsih’s writing already highlighted problems of women, street children, and poverty. Her awareness and perspective on gender is a process conducted through the experience of reporting, discussions, and reading books related to gender. In the case of 'Maria', Kompas as an institution provides her with freedom to pour her thoughts.